2019
DOI: 10.1002/sctm.18-0178
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Wound Healing Effects of Mesenchymal Stem Cell Secretome Delivered Within a Viscoelastic Gel Carrier

Abstract: Severe corneal injuries often result in permanent vision loss and remain a clinical challenge. Human bone marrow‐derived mesenchymal stem cells (MSCs) and their secreted factors (secretome) have been studied for their antiscarring, anti‐inflammatory, and antiangiogeneic properties. We aimed to deliver lyophilized MSC secretome (MSC‐S) within a viscoelastic gel composed of hyaluronic acid (HA) and chondroitin sulfate (CS) as a way to enhance corneal re‐epithelialization and reduce complications after mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 39 publications
1
66
0
2
Order By: Relevance
“…For example, in preclinical models, MSC‐CM distributed within a hyaluronic acid (HA) hydrogel enhanced tissue regeneration after endometrial injury, [ 21 ] while a hydrogel composed of HA and chondroitin sulfate incorporating MSC‐CM achieved corneal wound healing. [ 208 ] Additionally, injection of MSC‐CM encapsulated in a platelet‐rich plasma hydrogel ameliorated renal healing and function in an acute kidney injury model, [ 209 ] while MSC‐CM delivered in synthetic PLGA nanoparticles coated with red blood cell membranes enhanced liver regeneration. [ 210 ] Several studies have demonstrated the potential of biomaterial‐based delivery of MSC‐EVs [ 211 ] for repair in indications such as peripheral nerve injury, [ 212 ] epidural fibrosis, [ 213 ] and incisional hernia [ 214 ] ( Table 2 ).…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…For example, in preclinical models, MSC‐CM distributed within a hyaluronic acid (HA) hydrogel enhanced tissue regeneration after endometrial injury, [ 21 ] while a hydrogel composed of HA and chondroitin sulfate incorporating MSC‐CM achieved corneal wound healing. [ 208 ] Additionally, injection of MSC‐CM encapsulated in a platelet‐rich plasma hydrogel ameliorated renal healing and function in an acute kidney injury model, [ 209 ] while MSC‐CM delivered in synthetic PLGA nanoparticles coated with red blood cell membranes enhanced liver regeneration. [ 210 ] Several studies have demonstrated the potential of biomaterial‐based delivery of MSC‐EVs [ 211 ] for repair in indications such as peripheral nerve injury, [ 212 ] epidural fibrosis, [ 213 ] and incisional hernia [ 214 ] ( Table 2 ).…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…Fluorescein dye strips (Haag-Streit, Koeniz, Switzerland) were infused in saline (2 strips per 1 mL saline), and then the liquid mixture was applied to the corneas to determine the location and degree of the ocular surface staining under cobalt blue illumination. Photographs of fluorescein-stained corneas were taken with a smartphone ophthalmic imaging adapter (Paxos Scope, by Digisight Technologies, now Verana Health, San Francisco, CA, USA) equipped with a 15 × magnifying lens and a blue LED in the same manner as done in previous research [22].…”
Section: Rabbit Cornea Organ Culturementioning
confidence: 99%
“…18 Human bone marrow-derived MSC secretome, consisting of cellderived soluble factors and extracellular vesicles delivered within a viscoelastic gel carrier combining HA and chondroitin sulfate, enhanced epithelial cell proliferation and wound healing following mechanical and chemical injuries to the cornea. 63 HA was present at higher levels in the AM stroma, and AM-derived stromal cells produced more HA in medium than did AM epithelial cells and skin-derived fibroblasts. 9,64 These data imply that the secretome contained within AMF-sup and HA promoted wound healing in the in vitro and in vivo models used in this study.…”
Section: Discussionmentioning
confidence: 84%